Hubungan Antara Keterampilan Metakognitif dan Kemampuan Berpikir Kritis pada Siswa SMP - Andriana Stevianggi Kusuma Wardhani; Heru Astikasari Setya Murti (EduInovasi: Journal of Basic Educational Studies, 2026)
This study aims to analyze the relationship between metacognitive skills and critical thinking ability among junior high school students. The main focus of the study is to identify how metacognitive skills, as a form of awareness and self-regulation in thinking, contribute to students’ critical thinking ability during early adolescence. The study employed a quantitative approach with a correlational research design. The participants consisted of 42 junior high school students aged 12–15 years from Tengaran District, selected using purposive sampling. Data were collected using two standardized instruments: the Metacognitive Skills Scale (27 items; α = 0.977) and the Critical Thinking Scale based on Facione’s theory (20 items; α = 0.970). Data analysis was conducted using Spearman’s correlation test due to non-normal data distribution. The results revealed a very strong positive relationship between metacognitive skills and critical thinking ability (r = 0.894; p < 0.01). These findings indicate that the higher students’ ability to plan, monitor, and evaluate their thinking processes, the higher their critical thinking ability. The results emphasize the importance of implementing metacognitive-based learning strategies, such as self-reflection, learning monitoring, and guided discussion, to enhance students’ critical thinking skills at the junior high school level. This study contributes empirical evidence to the field of cognitive psychology by affirming the role of metacognition as a key predictor of critical thinking in early adolescence and provides a conceptual foundation for the development of 21st-century learning interventions.